Ubicación de las humanidades y la filosofía - Estrella, Jorge (Revista Chilena de Humanidades, 2015)
Professor Estrella notes the fact th at when an attempt is made to place the humanities within the field of knowledge, the problem of the unity 01 diversity of reality is reawakened. On this basis, he refers to some significant attempts to differentiate natural sciences from the science of the spirit, in spite of which, he points out, they are gettin g ever closer to one another. In agreement with Piaget, he regroups the humanities thus: nomothetical sciences, which attempt to establish laws, and properly historical, juridical and philosophical sciences, stating that philosophy stands at the outennost boundaries of the knowledge made use of by the other sciences, and that it is te be found within the core of the Humanities and also in that of any other scientific effort, not to impose its authority but to contribute towards the purpose of each one of them.